Pharmacokinetic analysis of thymol, carvacrol and diallyl disulfide after intramammary and topical applications in healthy organic dairy cattle. Issue 5 (4th May 2017) - Mason, Sharon E.; Mullen, Keena A. E.; Anderson, Kevin L.; Washburn, Steven P.; Yeatts, James L.; Baynes, Ronald E.
ABSTRACT: Mastitis is among the most costly concerns for dairy producers whether cattle are managed conventionally or organically. Unfortunately, there are no USFDA-approved mastitis treatments that allow dairy cows in the United States to maintain organic dairy status. We investigated the plasma pharmacokinetics of three organic mastitis products currently used by organic producers and organic dairy veterinarians. Those products include intramammary, topical and intravaginal preparations, each dosed at two levels. Additionally, tissue data were collected for kidney, liver and fat in order to estimate a withholding time for each of the products. The lower limit of quantification (LOQ) and lower limit of detection (LOD) were 0.001 and 0.0005 µg ml –1, respectively, in plasma and all tissues except fat for both thymol and carvacrol. Fat had an LOQ of 0.01 µg ml –1 and an LOD of 0.005 µg ml –1 for thymol and carvacrol. Diallyl disulfide had an LOQ of 0.005 µg ml –1 and LOD of 0.001 µg ml –1 in all tissues. For diallyl disulfide (garlic), no levels above 0.001 µg ml –1 were measurable in plasma or tissues. For topical and intramammary products, levels were measurable in the plasma, liver, kidney and fat up to 72 h after the last dose. The plasma half-lives were short for thymol (approximately 1.6 h) and carvacrol (approximately 1.5 h), whereas the estimated half-lives for these substances in tissues ranged from 13.9 to 31.5 h for thymol and from 16.9 to 25 h for carvacrol. The predicted amount of time that the molecules would be found in the body based on the slowest depletion time of liver tissue was 13 days for thymol and 10 days for carvacrol. The apparent half-life of topically applied carvacrol was approximately 4.5 h in plasma, with an estimated withhold time of 10 days. These times were calculated using the USFDA's tolerance limit method for meat withdrawal times.